(untitled) (Singaporean Journal of Business Economics and Management, 2013)
This research explores the prevalence of stress and burnout in Mental Healthcare Workers (MHCWs), as well as the physical, psychological, and emotional consequences of stress and burnout to the employee and the organization. The researcher hypothesizes that MHCWs in a KwaZulu-Natal (KZN) psychiatric hospital are under a significant amount of stress and burnout, thus leading to certain managerial challenges within the organization. A quantitative study was undertaken with the application of the Stress Diagnostic Survey and the Maslach Burnout Inventory as the research instruments. Surveys were delivered to 120 doctors and nurses (MHCWs) currently managing patients in the psychiatric wards in a KZN psychiatric hospital, as well as interviews conducted on five operational managers. The empirical findings of this study do not indicate that MHCWs are significantly more stressed than a sample of 41 community service doctors in KZN, or more burnt-out than a sample of 1104 healthcare professionals as specified in the Maslach Burnout Inventory. Although MHCWs are experiencing high levels of stress and burn-out, it is not of a significant degree. It is critical that hospital management identifies and acknowledges the effects of stress and burn-out on MHCWs and on the organization, and implements the necessary stress-reduction interventions.